2022
DOI: 10.3389/fped.2022.987523
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between screen viewing and sleep quality for infants and toddlers in China: A cross-sectional study

Abstract: AimCurrently young children have more opportunity to access all kinds of media, while their sleep duration has been steadily decreasing. However, little is known about the relationships between screen viewing and sleep quality, and the reasons of screen viewing for children under three years old in China. This study aimed to describe the relationships between screen viewing and sleep quality of infants and toddlers in mainland China.MethodsA cross-sectional study was conducted. Eight hundred twenty-seven child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Moreover, a questionnaire-based study found that ST influences sleep in infants and toddlers. No ST was linked with more total sleep time compared to any duration of ST in children aged 0-2 yo [57]. Toddlers also seem to be affected by excessive ST. More than 1 h daily of TV led to increased sleep problems.…”
Section: Sleep and Physical Activitymentioning
confidence: 84%
“…Moreover, a questionnaire-based study found that ST influences sleep in infants and toddlers. No ST was linked with more total sleep time compared to any duration of ST in children aged 0-2 yo [57]. Toddlers also seem to be affected by excessive ST. More than 1 h daily of TV led to increased sleep problems.…”
Section: Sleep and Physical Activitymentioning
confidence: 84%
“…However, we also found that the proportion of meeting ST recommendations in children who attended ECE classes is lower than in those who did not. Different from Western countries, parents in Asia believe that ST benefits their children’s learning [ 33 ]. Similarly, evidence has shown screen viewing for education was the greatest motivation for parents who reported not meeting guidelines [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive screen time affects the quality of sleep, by disrupting melatonin secretion due to blue-light emission, which may manifest with delayed onset of sleep, frequent awakenings, and nightmares, resulting in an abnormal sleep pattern [ 15 , 22 , 38 ]. A study by Lin et al revealed a negative correlation between screen exposure and total and nighttime sleep for infants and toddlers alike [ 38 ].…”
Section: Reviewmentioning
confidence: 99%
“…Excessive screen time affects the quality of sleep, by disrupting melatonin secretion due to blue-light emission, which may manifest with delayed onset of sleep, frequent awakenings, and nightmares, resulting in an abnormal sleep pattern [ 15 , 22 , 38 ]. A study by Lin et al revealed a negative correlation between screen exposure and total and nighttime sleep for infants and toddlers alike [ 38 ]. Moreover, excess screen time promotes a sedentary lifestyle for children, reducing the time they spend on outdoor or other indoor physical activities, that otherwise help towards building a healthy sleep pattern [ 38 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation